KELAYAKAN PERMINTAAN KEDELAI (Glycine max L. Merril) DI KABUPATEN BUNGO - F Fikriman; Reza Fahlevi; Widuri Susilawati (Fapetrik-UMPAR, 2019)
Soybeans play a very important role as a food ingredient due to their nutritional value and high protein content. The purpose of this study is to analyze the influence of price, population and per capita income factors on soybean demand in Bungo District and to analyze the elasticity of soybean demand in Bungo District. The selection of places in Bungo Regency as the object of research was carried out purposively (deliberately) with consideration of the location of the study as one of the soybean producing regions and also the area that used soybeans as raw material for industrial products. The method used in this research is descriptive method of describing the analysis of the analysis itself where the data was collected factually from the Central Statistics Agency (BPS), the Food Crops Office and the Bungo Regency Industry and Trade Service Office which were then tabulated for analysis. There is no joint effect between soybean price variable (X1), population (X2) and per capita income (X3) on soybean demand dependent variable (Y), and only free income per capita variable which has partial effect on demand dependent variable soybeans and price elasticity are elastic with a value of 1.93, while income elasticity is inelastic with a value of 0.52.